1984
DOI: 10.1016/0092-8674(84)90538-5
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence of the heat shock regulatory gene of E. coli suggests its protein product may be a transcription factor

Abstract: We have sequenced a cloned segment of E. coli chromosomal DNA that includes the heat shock regulatory gene htpR. This segment contains an 852 nucleotide open reading frame bounded by transcriptional and translational signals. Both in vivo and in vitro the cloned segment produces a single protein that migrates in gels with the cellular protein (F33.4) implicated as the htpR product. Properties of a cloned fragment of the coding sequence truncated at the promoter-distal end are consistent with this assignment. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
126
0
1

Year Published

1985
1985
2007
2007

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(129 citation statements)
references
References 25 publications
2
126
0
1
Order By: Relevance
“…Induction of the heat shock response is regulated at the level of transcription. In E. coli, the heat shock genes are positively regulated by the rpoH gene, whose product, a 32-kDa sigma factor, directs core RNA polymerase to recognize the promoters for heat shock genes (12,25,34). In B. subtilis, only one transcription start site is preceded by a promoter sequence recognized by sigma-43, the vegetative sigma factor.…”
Section: Discussionmentioning
confidence: 99%
“…Induction of the heat shock response is regulated at the level of transcription. In E. coli, the heat shock genes are positively regulated by the rpoH gene, whose product, a 32-kDa sigma factor, directs core RNA polymerase to recognize the promoters for heat shock genes (12,25,34). In B. subtilis, only one transcription start site is preceded by a promoter sequence recognized by sigma-43, the vegetative sigma factor.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that Streptomyces, like E. coli (Grossman et al, 1984;Landick et al, 1984), Bacillus (Losick & Pero, 1981) and recently the mntrogen-regulated genes of enteric bacteria (Hirschman et al, 1985) possess multiple sigma (C) factors (Westpheling et al, 1985;Buttner & Brown, 1985) which are each believed to initiate transcription from a specific class of promoter. In S. coelicolor one of the a-factors identified, probably the o.40 found by Buttner & Brown (1985) or o45 of Westpheling et al (1985), may be analogous to the E. coli a`70 factor that recognizes the consensus promoter of TTGACA (-35 region) and TATAAT (-10 region), and may be partly responsible for the capacity of Streptomyces to recognize and initiate transcription from promoters derived from a diverse source of bacteria including E. coli (Bibb & Cohen, 1982;Jaurin & Cohen, 1984;Westpheling et al, 1985;Herbert et al, 1986).…”
Section: Streptomyces Lividansmentioning
confidence: 99%
“…Understanding this mode of regulation is central to our understanding of protein quality control as well as cellular stress responses. Here, we report the determinants required for chaperone regulation of 32 , the heat shock transcription factor in Escherichia coli (10)(11)(12). 32 regulon members control both the activity and stability of 32 .…”
mentioning
confidence: 99%